Kemampuan Literasi Digital Orang Tua Dalam Mengasuh Anak: Studi Kasus Di Desa Curug, Gunung Sindur, Bogor - Hidayat, Parhan (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2023)
This research aims to find out parents' abilities in Islamic parenting,Â Â their digital literacy skills, and whether there is an influence of Islamic parenting skills on parents' digital parenting skills. This research was carried out with a quantitative approach using simple regression analysis. Respondents in this study totaled 58 people. The sampling technique used was a purposive sampling technique where the respondents selected were parents who met 2 main criteria. First, parents already have children who are at least 3 years old and above. Second, parents have the ability to use cell phones or other gadgets to access the internet. The research results show that parents' abilities in Islamic parenting are very high, reaching a score of 3.34. Likewise, in terms of digital parenting, parents' abilities are also quite high because they reach a score of 3.1. Then regarding the question of whether there is an influence of Islamic parenting skills on digital parenting, the answer is that there is a very significant influence, namely 0.81344502 from the results of using the Pearson product-moment formula.